2013
DOI: 10.1055/s-0033-1335518
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Breast as Part of the Assessment in Population-Based Mammography Screening

Abstract: Purpose: To evaluate the indications and impact of MRI of the breast as an assessment modality in population-based mammography screening. Materials and Methods: 135 consecutive contrast-enhanced MRI exams of the breast, which were performed between April 2007 and October 2012 as part of the assessment at one mammography screening unit before issuance of a final management recommendation (e.?g. definitely benign or malignant), were retrospectively reviewed. Overall, the cases with an MRI exam of the breast dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Studies included primarily unclear BI-RADS 0 or 3 finding analogs, whereas some studies also included lesions labeled as BI-RADS 4. In the latter, however, the lesions could not be localized for biopsy and as such qualify as equivocal lesions [ 13 , 18 , 23 ]. Four studies indicated detailed reasons for referral to breast MRI (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies included primarily unclear BI-RADS 0 or 3 finding analogs, whereas some studies also included lesions labeled as BI-RADS 4. In the latter, however, the lesions could not be localized for biopsy and as such qualify as equivocal lesions [ 13 , 18 , 23 ]. Four studies indicated detailed reasons for referral to breast MRI (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies indicated detailed reasons for referral to breast MRI (e.g. the exact type of clinical or imaging findings) [ 15 , 23 , 25 , 26 ], two of which stratified breast MRI results by indication [ 25 , 26 ]. The remaining ten studies did not specify detailed indications for breast MRI referral [ 13 , 16 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent German article from Bick et al . reported detection of 30 malignancies in 28 patients (2 bilateral) from 135 consecutive MRI studies (22%) with an overall PPV of 53%, and observed that MRI was used in less than 2% of all assessment cases …”
Section: Discussionmentioning
confidence: 99%
“…To summarise, use of problem‐solving breast MRI is not advocated for indeterminate lesions that can be readily biopsied such as palpable or sonographic masses or microcalcifications. Equivocal findings where MRI may be appropriate include subtle asymmetric densities, particularly if seen on only one projection, with this group accounting for almost half of cases in previous studies . Architectural distortion should always be regarded with suspicion but differentiation from summation artefact is problematic.…”
Section: Discussionmentioning
confidence: 99%